How interpretation makes international law : on semantic change and normative twists - Venzke, Ingo (OUP OxfordGB, 2012)
Introduces a theoretical perspective on the practice of intepretation for better understanding and analysis. Critiques past approaches to lawmaking in communicative practices, tackles the question of how interpretation can be both creative as well as constrained, and introduces the space of interpretation as a site for the exercise of power and authority.